2018
DOI: 10.1002/ardp.201800200
|View full text |Cite
|
Sign up to set email alerts
|

Some pyrazoles derivatives: Potent carbonic anhydrase, α‐glycosidase, and cholinesterase enzymes inhibitors

Abstract: A series of substituteed pyrazol‐4‐yl‐diazene derivatives were found to be effective inhibitors against α‐glycosidase, cytosolic carbonic anhydrase I and II isoforms (hCA I and II), butyrylcholinesterase (BChE), and acetylcholinesterase (AChE) with Ki values in the range of 33.72 ± 7.93 to 90.56 ± 27.52 nM for α‐glycosidase, 1.06 ± 0.16 to 9.83 ± 0.74 nM for hCA I, 0.68 ± 0.12 to 7.16 ± 1.14 nM for hCA II, 44.66 ± 10.06 to 78.34 ± 17.83 nM for AChE, and 50.36 ± 13.88 to 88.36 ± 20.03 nM for BChE, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 50 publications
(62 reference statements)
1
36
0
Order By: Relevance
“…It is found that the CS‐adsorbed PP film shows a new band at 1554 cm −1 corresponding to the NH bending vibration, which decreases when CS amino groups interact with the AgNP surface for the AgNP x /CS‐coated PP film. This behavior agrees with the fact that the coordination complex limits the NH vibrational mode and its intensity decreases . The surface functional groups of AgNP x /CS‐coated PP films were also analyzed from the absorbance band ratio from the amino to the methylene group (A15560.62emcm1/A14560.5emcm1).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…It is found that the CS‐adsorbed PP film shows a new band at 1554 cm −1 corresponding to the NH bending vibration, which decreases when CS amino groups interact with the AgNP surface for the AgNP x /CS‐coated PP film. This behavior agrees with the fact that the coordination complex limits the NH vibrational mode and its intensity decreases . The surface functional groups of AgNP x /CS‐coated PP films were also analyzed from the absorbance band ratio from the amino to the methylene group (A15560.62emcm1/A14560.5emcm1).…”
Section: Resultssupporting
confidence: 76%
“…The antimicrobial activity can be imparted to materials employing compounds that reduce or inhibit the growth of microorganisms, without showing general toxicity in the surroundings of the treated center . The antibacterial agents (antibiotics) most commonly used come from completely natural products, such as aminoglycosides; chemically modified natural compounds, such as penicillin, cephalosporin, or carbapenem; and completely synthetic ones, such as sulfonamides . However, the widespread use of these substances and their abuse have led, in many cases, to bacterial resistance, a growing issue that calls for the development of new strategies .…”
Section: Introductionmentioning
confidence: 99%
“…CA enzymes are classical which are inhibited by different compounds with a sulfonamide‐based (SO 2 NH 2 ) zinc‐binding group or their bioisosteres such as sulfamides and sulfamates. As CA II enzymes are the most physiologically plentiful isoforms, which they were mostly recorded as the predominant off‐purpose isozymes of which inhibitions were eschewed . Recently, multiple kinds of compounds have been searched as nonclassical CAIs, including polyamines, coumarins, phenols, carboxylic acids, fullerenes, and their derivatives …”
Section: Resultsmentioning
confidence: 99%
“…[56,57] The influence of phenolic compounds on metabolic enzymes is at the last period and the results of the inhibition of phenolic compounds are found in the literature. [58][59][60][61]…”
Section: Discussionmentioning
confidence: 99%